2012
DOI: 10.1016/j.hrthm.2012.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol infusion in the vein of Marshall facilitates mitral isthmus ablation

Abstract: Background Treatment of perimitral flutter (PMF) requires bidirectional mitral isthmus (MI) block, which can be difficult with radiofrequency ablation (RFA). The vein of Marshall (VOM) is located within the MI. Objective To test whether VOM ethanol infusion could help achieve MI block. Methods Perimitral conduction was studied in patients undergoing ablation of atrial fibrillation (AF). Group 1 included 50 patients with a previous AF ablation undergoing repeat ablation, 30 of which had had MI ablation. Spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 141 publications
(165 citation statements)
references
References 32 publications
4
142
1
Order By: Relevance
“…12, 26, 41, 43 In our in toto experience of 165 patients has an overall success of VOM cannulation and ethanol delivery in 89% (unpublished data). The initial step includes CS cannulation with a suitably large sheath (usually 7F sheath) preferably via the right internal jugular vein, although femoral or left subclavian vein approaches can be successful.…”
Section: Vom Ethanol Infusionmentioning
confidence: 89%
“…12, 26, 41, 43 In our in toto experience of 165 patients has an overall success of VOM cannulation and ethanol delivery in 89% (unpublished data). The initial step includes CS cannulation with a suitably large sheath (usually 7F sheath) preferably via the right internal jugular vein, although femoral or left subclavian vein approaches can be successful.…”
Section: Vom Ethanol Infusionmentioning
confidence: 89%
“…Additionally, the VOM sits on the epicardial aspect of the left atrial ridge and the mitral isthmus – a critical region sustaining perimitral flutter. We showed that VOM ethanol infusion can lead to effective ablation of this region and cure of perimitral flutter [46]. Finally, we demonstrated that the abundant para-sympathetic innervation of the VOM and the neighboring atrial epicardium can be ablated by VOM ethanol infusion [47 ■ ] (see Fig.…”
Section: Using the Venous Route For Ethanol Deliverymentioning
confidence: 99%
“…4 Herein, we report the first proof a mechanistic role of VOM in recurrent PMF, by showing epicardial signals from the VOM in areas endocardially ablated, and the successful treatment by ethanol infusion.…”
Section: Discussionmentioning
confidence: 78%